1995
DOI: 10.1093/nar/23.12.2229
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and regulatory effects of transcription factors SP1 and USF at the rat amyloid precursor protein gene promoter

Abstract: Two DNA elements which we have termed SAA and GAG have been shown to control expression of the rat amyloid precursor protein (APP) gene, and the region containing the SAA element has been shown to interact with nuclear proteins [Hoffman and Chernak (1994) Biochem. Biophys. Res. Commun. 201, 610-617]. In this report we study DNA sequences and proteins which influence the activity of the SAA element. An oligonucleotide containing the SAA element is specifically bound by nuclear proteins derived from rat PC12 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 20 publications
2
41
0
1
Order By: Relevance
“…Such motifs have been reported to be potential binding sites for basic helix-loop-helix (bHLH) transcription factors, c-myc, Myo D, and ubiquitous transcription factors USF-1 and USF-2 proteins (Maekawa et al 1991, Hoffman & Chernak 1995, Elnitski et al 1997, Gao et al 1997, Gupta et al 1997, Scholtz et al 1997. Previous studies have demonstrated that E2 transiently induces c-myc gene expression in MCF-7 cells, and a synthetic antisense c-myc oligonucleotide partially inhibited E2-induced growth of MCF-7 cells (Dubik et al 1987, Watson et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Such motifs have been reported to be potential binding sites for basic helix-loop-helix (bHLH) transcription factors, c-myc, Myo D, and ubiquitous transcription factors USF-1 and USF-2 proteins (Maekawa et al 1991, Hoffman & Chernak 1995, Elnitski et al 1997, Gao et al 1997, Gupta et al 1997, Scholtz et al 1997. Previous studies have demonstrated that E2 transiently induces c-myc gene expression in MCF-7 cells, and a synthetic antisense c-myc oligonucleotide partially inhibited E2-induced growth of MCF-7 cells (Dubik et al 1987, Watson et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the ATF/CRE site is essential for the COX-2 expression induced by v-src, serum, and platelet-derived growth factor in NIH3T3 cells (21)(22)(23), whereas the E-box was required for COX-2 expression in rat ovarian granulosa cells in response to various hormones (18). When nuclear extracts of JWF2 cells were incubated with the radiolabeled ATF/ CRE⅐E-box oligonucleotides in the presence of wild-type, mutant, and consensus oligonucleotides of CREB (32) or E-boxbinding protein USF (33), the protein-DNA complexes were completely competed out by consensus USF oligonucleotides (Fig. 4A, seventh lane), whereas consensus ATF/CRE oligonucleotides had no significant effect on the binding (Fig.…”
Section: Murine Cox-2 Promoter Contains Two Positive Regulatorymentioning
confidence: 99%
“…The proximal APP promoter region also contains an sp1 site (25,26) and two nuclear factor binding domains designated as APB␣ and APB␤ (27). The factors that bind to these domains display sequence specificity, and it was demonstrated that the primary cellular factor that binds to APB␣ is a heterodimer of USF43 and USF44 (25, 28 -30).…”
mentioning
confidence: 99%